The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/rs8050408
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Categorical Land Use Transition and Land Degradation in Northwestern Drylands of Ethiopia

Abstract: Land use transition in dryland ecosystems is one of the major driving forces to landscape change that directly impacts the welfare of humans. In this study, the support vector machine (SVM) classification algorithm and cross tabulation matrix analysis are used to identify systematic and random processes of change. The magnitude and prevailing signals of land use transitions are assessed taking into account net change and swap change. Moreover, spatiotemporal patterns and the relationship of precipitation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 67 publications
(112 reference statements)
4
19
0
Order By: Relevance
“…In agreement with the results of this study, earlier studies in the region (Ariti et al 2015;Biazin & Sterk 2013;Garedew et al 2009;Kindu et al 2013;Meshesha et al 2012;Temesgen et al 2013) and studies elsewhere in the country (Hailemariam et al 2016;Reid et al 2000;Tefera 2011;Zeleke & Hurni 2001;Zewdie & Csaplovics 2016) also particularly indicated a decline in the acacia woodlands/forests and an increase in agricultural land in recent decades. The gain in agricultural land is mainly associated with the continual expansion of cropland with population growth, as population growth is the primary driver of LULCC in developing countries (Ariti et al 2015;Braimoh 2006;Garedew et al 2009;Meshesha et al 2012).…”
Section: Comparison Of Perceived and Observed Land Use-land Cover Chasupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the results of this study, earlier studies in the region (Ariti et al 2015;Biazin & Sterk 2013;Garedew et al 2009;Kindu et al 2013;Meshesha et al 2012;Temesgen et al 2013) and studies elsewhere in the country (Hailemariam et al 2016;Reid et al 2000;Tefera 2011;Zeleke & Hurni 2001;Zewdie & Csaplovics 2016) also particularly indicated a decline in the acacia woodlands/forests and an increase in agricultural land in recent decades. The gain in agricultural land is mainly associated with the continual expansion of cropland with population growth, as population growth is the primary driver of LULCC in developing countries (Ariti et al 2015;Braimoh 2006;Garedew et al 2009;Meshesha et al 2012).…”
Section: Comparison Of Perceived and Observed Land Use-land Cover Chasupporting
confidence: 93%
“…Furthermore, due to recurrent drought and hence low income and food insecurity problem in recent years, rural farmers of the study area use charcoal and firewood market as a substitute source of income, which is taken as the adaptation mechanism to overcome such critical periods (Kindu et al 2015). Previous studies in Ethiopia also mentioned charcoal making and fuelwood extraction as a key factors for the decline of acacia woodlands in the country (Ariti et al 2015;Garedew et al 2009;Molla 2015;Zewdie & Csaplovics 2016), whereas study in West Africa pointed timber logging as the main proximate cause for woodland decline in Ghana (Braimoh 2006), which is inconsistent with our result.…”
Section: Fuelwood Extraction and Charcoal Makingmentioning
confidence: 96%
“…These are detecting changes in the landscape first, and then ascribing that change to some set of casual factors. The importance of addressing systematic and random LULC transitions has been further evidenced by recent studies (Burmeister and Schanze, 2016;Zewdie and Csaplovics, 2016;Briones and Sepúlveda-Varas, 2017). Linking the studies of changes in landscape pattern to the processes underlying helps to better understand the mechanisms of change; generate predictions about future rates of change, identify potential vulnerable places to change, and to design appropriate policy responses (Lambin, 1997;Nagendra et al, 2004;Alo and Pontius Jr, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Ethiopia is one of the typical countries in the sub-Saharan Africa confronted with the multidirectional impacts of extensive and rapid LULC dynamics since the beginning of the twentieth century (Kindu et al, 2013;Lemenih and Kassa, 2014 empirical studies shown that deforestation in Ethiopian highlands has changed the landscape from 40% of forest cover in 1900 to 3.2% cover in 1980 (Dessie and Kleman, 2007;Eshetu, 2014), though some unpublished sources reported an increase in forest coverage of the country since 2000. On the other hand, significant increase in agricultural lands in expense of losses in forestlands, woodlands and grasslands has been reported in arid and semi-arid areas of the country including the Central Rift Valley (CRV) Lakes Region (Muzein, 2006;Garedew et al, 2009;Temesgen et al, 2013;Meshesha et al, 2014;Ariti et al, 2015;Zewdie and Csaplovics, 2016). In addition, in recent years, expansion in built-up areas has also been accelerated in Ethiopia since the government change and subsequent land use policy reforms in 1991 (Meire et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation